Pothos (Epipremnum aureum) Diseases: Identification and Control in Commercial Greenhouse Production - David J. Norman; Gul Shad Ali (EDIS)
Pothos is a tropical ornamental vine that has been grown commercially in the US for almost 100 years and is used for a variety of aesthetic purposes. This 5-page publication addresses identification and treatment of common diseases encountered during greenhouse production of pothos. Written by David J. Norman and G. Shad Ali and published by the UF/IFAS Plant Pathology Department, July 2018. http://edis.ifas.ufl.edu/pp340